Palavra encena ato em canto; palavra em cena, ato encanto : uma leitura da poética da Cia. Teatro Balagan em Prometheus - a tragédia do fogo - Cecchini, Giselle Molon (2017)
This dissertation has a starting point the chanting in Prometheus – a tragédia do fogo (Prometheus – The Tragedy of Fire). The play created by the Cia. Teatro Balagan, from São Paulo, is written by Leonardo Moreira and staged by Maria Thaís Lima Santos. The present study starts from chanting, in its many names, first considering it as integrating voice, word and performance. As language, chanting is a vehicle of a memory, of an art. The polysemic term “chanting”, runs through the object of study and finds its meaning according to the context in its many senses. My argument is based on the following aspects: 1. Chanting as poetry – in its dramatic, epic and lyric genres. Chanting is myth itself; 2. Chanting on stage – physical, vocal and verbal action (voice/word/body/action); chanting as word sung, in its poetic principles, its orality, vocality and performance; chanting as music composition; 3. The chanting of the scene – a crossing of the distinct voices on the polyphonic staging of Prometheus. This work is defined by the dialogue between areas of Theater studies, with its multiple signs, and Literature studies. Unfolding into many subjects, chanting reveals itself as a strategy for approaching and reading the staging poetics of Cia. Teatro Balagan in Prometheus - a tragédia do fogo.